Why don't U.S. issuers demand European fees for IPOs? - Abrahamson, M; Jenkinson, T; Jones, H (Wiley, 2011)
We compare the fees charged by investment banks for conducting IPOs in the U.S. and Europe. In recent years the “7% solution”, as documented by Chen and Ritter (2000), has become even more prevalent in the U.S., and is now the norm for IPOs raising up to 250m dollars. The same banks dominate both markets but European IPO fees are roughly three percent lower, are much more variable, and have been falling. We review explanations for the gap in spreads and find the evidence consistent with strategic pricing. U.S. issuers could have saved over 1bn dollars a year by paying European fees.